Effectiveness of Implementation of Employee Performance Targets (SKP)Based Online in the Governance Section Secretariat of the City of Yogyakarta - Sardini; Widyayanti, Evi Rosalina (Islamic Business and Management Journal, 2024)
This study focuses on observing the effectiveness of the implementation of online-based Employee Performance Targets (SKP) in the Governance Section of the Yogyakarta City Regional Secretariat, inhibiting factors and efforts made in order to optimally improve employee performance in the Governance Section of the Yogyakarta City Regional Secretariat. The author uses the theory of Gibson, Donnelly, and Ivancevich related to organizational effectiveness which is limited to the implementation of online-based Employee Performance Targets (SKP) and employee behavior. The author in conducting the study used a qualitative method with a descriptive approach. In collecting data, the author conducted observations, interviews using a list of questions given to informants, and documentation related to the implementation of online-based Employee Performance Targets (SKP). The results of the study indicate that the implementation of online-based Employee Performance Targets (SKP) in the Governance Section of the Yogyakarta City Regional Secretariat has been running well, seen from the process of implementing the preparation and supervision in the implementation of online-based Employee Performance Targets (SKP). Constraints related to limited human resources can be overcome by optimizing existing employees in completing work tasks. In order to improve employee performance, the efforts made are to involve employees in technical guidance or training, conduct evaluations of activity implementation to monitor and optimize performance achievements, create a comfortable work environment, and build effective communication. Keywords: Effectiveness, Online-Based SKP, Employee Performance.